Retroauricular endoscopic thyroidectomy: initial single-institution experiences - Yulian, Erwin Danil; Panigoro, Sonar Soni; Melati, Putri Arum (Updates in surgery, 2024)
Conventional thyroidectomy often results in visible scarring postoperatively. Endoscopic thyroidectomy offers the advantage of scarless surgery, especially beneficial for young adult women. The retroauricular approach uses a facelift incision well-known among surgeons and eliminates the need for gas insufflation due to the large working space. An early retrospective analysis was conducted on thirty-one individuals who underwent gasless retroauricular endoscopic thyroidectomy approach, focusing on isthmolobectomies ( n = 26) and lobectomies ( n = 5), with one case necessitating conversion to open thyroidectomy, from January 2016 to April 2017. Physical examination, laboratory, and histopathology findings were collected. The scar was evaluated using the Vancouver Scale System, while other surgical and oncological outcomes were documented and assessed. The average operative time was 154.2 ± 21.3 min, with an average bleeding volume of 69.2 ± 52.1 mL. The average length of stay was 4.7 ± 2.2 days. All complications occurred were temporary and all subjects remained in good condition throughout the follow-up period. Most subjects (65.6%) were very satisfied with the scar concealed in the retroauricular area. Retroauricular endoscopic thyroidectomy is a safe and feasible remote access technique with excellent postoperative results.